Situasi pembelajaran bahasa asing di institut pengajian tinggi : perbandingan antara Bahasa Arab, Bahasa Mandarin dan Bahasa Perancis - Azman Che Mat,; Goh, Ying Soon (Penerbit Universiti Kebangsaan Malaysia, 2010)
The teaching and learning of foreign languages aim to achieve numerous outcomes; among them is to enable students to communicate. Attitude and psychological factors form barriers in the success of foreign language communication skills among students. Previous studies of how attitude affects foreign language learning have been carried out by UiTM Terengganu as Arabic, Mandarin, and French are among foreign language courses offered in UiTM (Higher Learning Institutions) HLI. A meta-analysis of the findings is presented; highlighting several challenges and solutions which may be employed by foreign languages instructiors at school and HLI. In an effort to motivate the teaching and learning of foreign languages, a few practicable suggestions are given in view of the challenge that English language as ‘threatening’ language diversity needs